Pembinaan Administrasi Ibu Rumah Tangga terhadap Pertumbuhan Kesehatan anak di Perumahan Central Park Cikarang Utara - Rustianah, Rustianah; Permana, Indra; Rachmawati, Dian; Ardianto, Riski Eko (Jurnal Gotong Royong, 2024)
The Indonesian government launched a health program to deal with health problems, especially public health, with the POSYANDU program so that children under five get health that can be monitored early in the community environment. The program usually runs for 6 months and is usually carried out every three months due to lack of community resources in the implementation due to the large working area, to deal with these problems make the community a partner by applying the concept of community empowerment so that they can be independent and the level of human health in each region can increase. This study aims to find out and describe the concept of empowerment used in the implementation of the posyandu program with the health services of children under five in the RT 075 Housing area cikarang central park north cikarang. The research shows that health and administrative services, especially for mothers, aim to improve the quality of better data collection and good services, so there needs to be support from many parties, one of which is support from the government as the highest institution both financially, facilities and infrastructure, as well as coaching cadres.